Boundless Creativity: Vlogging with a Smartphone in the Digital Era - Kala'lembang, Adriani; Riska, Suastika Yulia; Widayanti, Lilis; Rahayu, Widya Adhariyanty; Fitria, Vivi Aida (Institut Teknologi dan Bisnis Asia Malang, 2025)
Purpose: This community service aims to enhance the technical skills of students at SMK Negeri 12 Malang in digital vlog creation. Method: The program involves training sessions using lectures and hands-on practice to improve lighting techniques. Practical Application: This initiative has a significant impact on vlog production by following essential steps, including framing techniques, lighting, and video editing. Conclusion: This program enhances students' creativity and skills in vlog creation.